2020
DOI: 10.2217/fca-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

The Selution SLR™ drug-eluting Balloon System for the Treatment of Symptomatic Femoropopliteal Lesions

Abstract: Endovascular treatment has become first line therapy for the treatment of femoropopliteal disease. Drug-coated devices play a key role in maintaining vessel patency. In the past antiproliferative coating of drug-coated balloons (DCBs) exclusively consisted of paclitaxel. Use of limus drugs was limited by a short residency time in the vessel wall. Besides the drug, the SELUTION SLR™ drug-eluting balloon system consists of a coating formulation of four excipients. The first excipient is a biodegradable polymer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 59 publications
(50 reference statements)
0
21
0
5
Order By: Relevance
“…Primary patency rate as assessed by Duplex ultrasound was 88.4% and freedom from restenosis was 91.2%. 12- and 24- month data (Böhme et al 2021 ) also demonstrated sustained improvement in 1 or more categories on the Rutherford Classification from baseline in 78% and 84% of patients at 12- and 24-months respectively and 85% freedom from TLR at 12-month post procedure. There were no incidence of major LEA or death at 24-months, although the patient cohort comprised of only claudicants (Böhme et al 2021 ).…”
Section: Present Evidence For Use Of Sirolimus Devicesmentioning
confidence: 90%
See 2 more Smart Citations
“…Primary patency rate as assessed by Duplex ultrasound was 88.4% and freedom from restenosis was 91.2%. 12- and 24- month data (Böhme et al 2021 ) also demonstrated sustained improvement in 1 or more categories on the Rutherford Classification from baseline in 78% and 84% of patients at 12- and 24-months respectively and 85% freedom from TLR at 12-month post procedure. There were no incidence of major LEA or death at 24-months, although the patient cohort comprised of only claudicants (Böhme et al 2021 ).…”
Section: Present Evidence For Use Of Sirolimus Devicesmentioning
confidence: 90%
“…New DCBs on the approval pathway mainly feature this new class of antirestenotic issues. At present, only the MagicTouch™ and the Selution SLR™ DCB have received approval for commercial distribution in Europe and granted FDA approval as a breakthrough device for treatment of lower limb PAD (Böhme et al 2021 ). Reimbursement for its use have thus far been variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome of late lumen loss at six months was significantly lower than the optimal performance outcome value of POBA. Six-month primary patency was 88.4% [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…With its long and successful history in coronary drug-eluting stents (DES), sirolimus has attracted the attention of researchers investigating new DCB technologies. Sirolimus-coated balloons have so far shown promising results in inhibition of restenosis after percutaneous coronary interventions (PCIs) in a small number of patients included in clinical studies [4][5][6][7][8]. Furthermore, a wide range of other drugs with potential antiproliferative, anti-inflammatory, or antithrombotic actions might be candidates for balloon coating.…”
Section: Introductionmentioning
confidence: 99%